When the story proceeds backward: The discovery of endogenous β-aminobutyric acid as the missing link for a potential new plant hormone. Issue 2 (4th March 2017) - Baccelli, Ivan; Mauch-Mani, Brigitte
ABSTRACT: The capacity of β-aminobutyric acid (BABA) to induce resistance in plants against biotic and abiotic stresses has been known for more than 50 y. In the beginning reports were mainly descriptive of the phenomenon, but it became clear with the discovery of BABA insensitive mutants in Arabidopsis that there was definitely a genetic basis underlying BABA-induced resistance. The study of these mutants, along with the use of regular hormone mutants, allowed establishing the defense pathways activated upon defense induction. To date it is clear that BABA potentiates the defense pathway more appropriate to counteract the upcoming stress situation, through a phenomenon termed priming. Interestingly, plants possess a receptor for BABA, but up to recently there was a general consensus on the fact that BABA was a xenobiotic molecule. The development of an accurate non-destructive assay for measuring aminobutyric acid isomers in planta and the finding of plant-produced BABA, thus seems to represent the missing link for the discovery of a novel plant hormone. Differences and similarities with some of the classical plant hormones are presented here.